Maternal resveratrol regulates the growth performance, antioxidant capacity, and intestinal health of suckling piglets through intestinal microorganisms at high summer temperatures - Zhao, Yi; Huang, Yujian; Gao, Kaiguo; Wen, Xiaolu; Hu, Shenglan; Wang, Li; Jiang, Zongyong; Xiao, Hao (Frontiers in Nutrition, 2022)
The study aimed to investigate the effects of dietary resveratrol supplementation under different thermal environments during late gestation and lactation on reproductive performance, antioxidant capacity, immune function and intestinal microbe and its relationship with immunoglobulin of colostrum in sows and piglets. Twenty sows were used in first phase experiment under moderate thermal environment, and the other twenty sows were used in second phase experiment under high thermal environment. Sows were fed a control diet or with 300 mg/kg resveratrol started at day 75 gestation. Plasma, milk, and feces samples were collected for the indexes of antioxidant capacity, immune function and intestinal microbe. The results showed that resveratrol supplementation respectively increased the number born alive 13.24% and 26.79% in the first and second phase, compared with the control group. In the second phase, resveratrol supplementation showed an increase in the litter weaning weight and the concentrations of growth hormone, insulin, progesterone, triglycerides and uric acid. Plasma SOD level on day 110 of gestation and on day 14 of lactation, GSH-PX on d 14 of lactation in first phase showed an increased trend (p=0.0728, p=0.0932, p=0.067, respectively) in the resveratrol group, compared with the control group. On day 14 of lactation, plasma T-AOC level was higher in the second phase, while plasma MDA level was lower in both phase in the resveratrol group. Resveratrol supplementation increased both the abundance of IgA, IgG and IgM of colostrum and the relative abundance of Lactobacillus and Alloprevotella, while decreased the relative abundance of Escherichia-shigella in piglets’ feces in the second phase. Furthermore, the Spearman correlation analysis indicated that weaned piglet weight gain was positively (P<0.05) associated with IgM content in colostrum and the abundance of Lactobacillus in fecal microbiota of piglets in the second phase. Moreover, Alloprevotella is positively correlated with the contents of IgA and IgG in colostrum, while the abundance of Lactobacillus abundance is positively with IgM content.These data indicated that maternal resveratrol supplementation could enhance growth performance, antioxidant capacity and intestinal healthy of piglets under high temperature environment, which might be associated with increasing the secretion of immunoglobulin of colostrum.